the PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARANTEKNOLOGI INFORMASI DI SMP PERGURUAN ADVENT 1 MEDAN - Asireli Telaumbanua; Ridwan Syahputra; Hukendik Hutabarat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of using technology-based learning media combined with the Project Based Learning approach on students' learning outcomes in the Information Technology subject at SMP Perguruan Advent 1 Medan. The problem addressed is the low student achievement caused by the lack of engaging learning media and less interactive teaching methods. The method employed is Classroom Action Research (CAR) conducted through two cycles of implementing technology-based media integrated with the Project Based Learning model. Learning outcome data were analyzed using mastery learning percentages. The results show a significant increase in students' learning mastery percentages, from 34.48% in the pre-cycle to 62.07% in cycle I, and reaching 86.21% in cycle II. The use of technology-based media facilitates students’ understanding of the material in an engaging, interactive, and contextual manner, thereby increasing motivation and learning involvement. The Project Based Learning approach, which emphasizes real project activities, encourages students to be more active, creative, and collaborative, positively impacting their academic achievement. The CAR cycles allow continuous evaluation and improvement, enabling the optimization of learning media and methods to suit students’ needs and classroom conditions. This study recommends the integration of technology-based media and innovative learning approaches to enhance the quality of Information Technology education.